Mechanistic Investigation of Biomimetic Non-Heme Iron Complexes for Oxidation Catalysis - Piquette, Marc. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Chemistry.; Advisors: Sergiy Kryatov, and Elena Rybak-Akimova.; Committee: Samuel Thomas, Arthur Utz, and John Caradonna.; Keyword: Inorganic chemistry.